2008
DOI: 10.1200/jco.2007.14.8114
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Clinical Communication on Patients' Decision Making on Participation in Clinical Trials

Abstract: In two urban, National Cancer Institute-designated comprehensive cancer centers, a large percentage of patients are not offered trials. When offered a trial, most patients enroll. The quality and quantity of communication occurring among the oncologist, patient, and family/companion when trials are discussed matter in the patient's decision-making process. These findings can help increase physician awareness of the ways that messages and communication behaviors can be observed and evaluated to improve clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
189
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(198 citation statements)
references
References 36 publications
6
189
0
3
Order By: Relevance
“…However, Bower and colleagues [11] highlighted that there was also a need to develop effective interventions aimed at those recruiting to trials. Although patient information leaflets are strictly regulated by ethics committees, the communication style of the recruiter (usually a clinician or nurse) plays an important role in patients' understanding of the information and their willingness to join the study [12]. Research has shown that information conveyed during recruitment appointments varies considerably in content and quality [13], and patients often have a poor understanding of RCT concepts [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, Bower and colleagues [11] highlighted that there was also a need to develop effective interventions aimed at those recruiting to trials. Although patient information leaflets are strictly regulated by ethics committees, the communication style of the recruiter (usually a clinician or nurse) plays an important role in patients' understanding of the information and their willingness to join the study [12]. Research has shown that information conveyed during recruitment appointments varies considerably in content and quality [13], and patients often have a poor understanding of RCT concepts [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Poor BBN may have a negative impact on patients' satisfaction with care [1], adherence to treatment [2], decisions about treatment options [3] and psychological adjustment [4]. Reviews about BBN have been published and there is now a wide consensus that BBN requires specific communication skills.…”
Section: Introductionmentioning
confidence: 99%
“…Patients prefer the doctor to make the treatment decisions rather than to be randomised. A recent report emphasises the influence of physicians' clinical communication on patients' decision-making on participation in clinical trials (Albrecht et al, 2008). Improving communication and more interventions by clinical research coordinators and other medical staff members in all eligible patients may improve the accrual rate (Fallowfield et al, 1998;Wright et al, 2004;Stryker et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The results of questionnaire surveys administered to patients regarding clinical trials revealed that two of the most common reasons for entering the trial were the hope for personal benefit and the opportunity to contribute to the research knowledge thereby benefiting others in the future (Jenkins and Fallowfield, 2000;Madsen et al, 2000Madsen et al, , 2002Ellis et al, 2001;Wright et al, 2004;Albrecht et al, 2008). On the other hand, the common reasons for declining participation were worries about the process of randomisation, overestimation of the benefits of standard therapy and fear of the trial's experimental nature (Jenkins and Fallowfield, 2000;Ellis et al, 2001;Ho et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation